Slametan Tradition in Javanese Society: A Perspective on Qur’anic Interpretation - Saifuddin Herlambang (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The Javanese community in Demak shows that the Slametan tradition is a means of social interaction and strengthening interpersonal and social relationships. Slametan is a religious and cultural ritual that forms the core of Javanese religious life. The purpose of Slametan is carried out for the safety of the Javanese people; this is in accordance with the word “Slamet,” which means salvation both physically and spiritually. The Slametan ritual on Islamic holidays is performed collectively in the mosque by reciting prayers together. This study aims to explore the Slametan tradition from the perspective of Qur’anic interpretation. This article is a descriptive-qualitative research project conducted through interviews, observations, and documentation on the Slametan tradition in Demak. This research was conducted on Javanese people in Karangawen District, Demak Regency, Central Java Province. The key finding in this study is that in the Slametan tradition carried out by the Javanese community in Demak, both values, practices, and goals have a theological foundation, namely the Qur’an. The findings of this study show that the purpose of Javanese people carrying out the Slametan tradition is to get God’s blessings